Analysis of the application of interactive learning media 3d model based on augmented reality - Jimmy Pratama; Helena Helena; Bayu Syahputra (Jurnal Pseudocode, 2026)
Technological developments have encouraged the use of Augmented Reality (AR) as an interactive learning medium in education. However, learning 3D animation using Autodesk Maya is still considered difficult by beginner students due to the complexity of the features and interface. This study aims to develop and analyze the benefits of an interactive learning media application based on markerless Augmented Reality (AR) in recognizing icons and functions of the Autodesk Maya Toolbox. The research method used is applied research with a qualitative approach and the Multimedia Development Life Cycle (MDLC) development method. The application was developed using Unity, Vuforia, and Autodesk Maya, and tested on 30 students through interviews. The results of the study show that the markerless AR application is able to help students understand and recognize the Autodesk Maya toolbox more easily through interactive and clear 3D object visualization. Thus, this application is considered useful as a supporting medium for innovative and interactive 3D animation learning.